Біоетика та досліди над тваринами - Койдан, А. А. (ХНУРЕ, 2021)
The work is devoted to scientific experiments on animals and ethics. It is a pity that today animals are the object of all kinds of experiments and tests. The consequences of such experiments threaten the survival of humanity and are much more serious than any other problem. You will find more detailed information on this topic in our theses.
Keywords: філософія; біоетика